2012
DOI: 10.18388/abp.2012_2189
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity of crude extracts containing carotenoids from the berries of various cultivars of Sea buckthorn (Hippophae rhamnoides L.).

Abstract: Comparative analysis of antioxidant capacity was performed using FRAP and DPPH methods on extracts containing carotenoids acquired from fruits of Sea buckthorn. The examination included nine varieties of Sea buckthorn growing in the comparative cultivation. Conducted analysis allowed to compare the antioxidant capacity with carotenoids content measured with spectrophotometric and HPLC methods. Three of the examined cultivars indicating high antioxidant activity in both, FRAP and DPPH methods, also revealed hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
3
15
1
3
Order By: Relevance
“…The results showed that total antioxidant activity of the fruits was 24.85 mM/100 g FW, which was higher than previous study (Kruczek et al 2012). The differences can be explained by differences in the environmental conditions of the regions under study which may affect the quality of the fruits.…”
Section: Resultscontrasting
confidence: 74%
“…The results showed that total antioxidant activity of the fruits was 24.85 mM/100 g FW, which was higher than previous study (Kruczek et al 2012). The differences can be explained by differences in the environmental conditions of the regions under study which may affect the quality of the fruits.…”
Section: Resultscontrasting
confidence: 74%
“…By comparison, in H. rhamnoides berries grown in Sweden, the carotene content was on average 29.66 mg/100 g DM [11]. On the other hand, research of Kruczek et al [35] indicated that Aromatnaja and Moskwiczka berries were rich in carotenes (average 23.01 mg/100 g FW), and Botaniczeskaja-Lubitelskaja, Luczistaja, and Podarok Sadu contained less than 1 mg/100 g FW.…”
Section: Analysis Of Carotenoids Tocopherols and Tocotrienols Of Sementioning
confidence: 91%
“…All three parameters are well correlated with Rvm by straight lines described by Eqs. (5)- (7), where determination coefficients (R 2 ) corresponding to them are 0.9747, 0.9916, and 0.9813, respectively. Substituting Eq.…”
Section: Mineral Elementsmentioning
confidence: 99%
“…200 components, is considered the most important part [2]. SB berries are rich in natural antioxidants, e.g., phenolic compounds (including flavonoids, phenolic acids, tocopherols), carotenoids (such as β-carotene, γcarotene, lycopene, zeaxanthin, lutein), ascorbic acid (vitamin C), which exhibit anti-inflammatory, anticancer, and antimicrobial effects [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Moreover, the berries are important sources of sugars (mainly glucose and fructose), proteins, organic acids (predominantly malic acid), aminoacids, essential fatty acids (FAs), volatile compounds, phytosterols (mainly β-sitosterol), and mineral elements (especially K, Mg, Ca, Na, and P) [2][3][4][5][6][7][8][9][10][12][13][14][15][17][18][19].…”
mentioning
confidence: 99%
See 1 more Smart Citation